Obstructive Sleep Apnea Syndrome (OSAS) Decrease Concentration Levels in Young Adults - Fidela Hanan Zivana; Neni Susilaningsih; Dwi Marliyawati; Kanti Yunika (Diponegoro International Medical Journal, 2020)
Background: Obstructive Sleep Apnea Syndrome (OSAS) is sleeping-disorder that’s characterized by recurrent episodes of upper airway obstruction during sleep. Fourteen percent of world populations suffer from OSAS. OSA patients are 7.5 to 20 times more likely to have difficulties with concentration, learning new tasks, and execution of monotonous tasks.Objective: The primary objective of this study was to investigate the relationship between Obstructive Sleep Apnea Syndrome (OSAS) and concentration level in young adultsMethods: This is an analytic observational study with cross-sectional design. Sampling was carried out with total sampling. Samples that qualified the inclusion and exclusion criteria were assessed by OSAS using the Epworth Sleepiness Scale (ESS) questionnaire and Digit Symbol Substitution Test was used to assess the concentration level. The data were analyzed, using the chi-square test and the prevalence (PR) testResults: The Chi-square test showed that there was a significant relationship between OSAS and concentration level (p=0.033). The Prevalence Ratio test found that OSAS decreased concentration level by 1.55 compared to not OSASConclusion: There was a significant relationship between OSAS and concentration level in young adults. OSAS patients are 1.55 more likely to have a decrease concentration level when compared with healthy individuals